Adolescent Reproductive Health Education: Midwives' Contribution to the Prevention of Unintended Pregnancy - Cynthia Puspariny; Chusnul Zulaika; Devin Mahendika; Nadia Purnama Dewi; Suyadi Suyadi (PT. Anagata Sembagi Education, 2025)
Unplanned pregnancy among adolescents is a complex issue influenced by limited access to reproductive health education and adolescent-friendly contraceptive services. This phenomenon has multidimensional impacts, including increased risk of health complications, school dropout, and social stigma that hinders adolescent well-being. The role of midwives is crucial in bridging the gap in information and access to reproductive health services. Evidence-based reproductive health education has been shown to be effective in improving adolescents' understanding of their sexual and reproductive rights. However, the implementation of this program still faces challenges in the form of cultural resistance, lack of training for health workers, and social stigma that hinders open discussion. This study uses a qualitative approach with a literature review method to analyze the role of midwives in preventing adolescent pregnancy. The results of the study show that cross-sector collaboration and the use of digital technology can increase the effectiveness of reproductive health education. However, challenges such as misinformation and weak digital regulations must be addressed by strengthening digital literacy and content monitoring. With the right strategy, midwives can play a more optimal role in providing inclusive and evidence-based services, so that adolescents are able to make responsible decisions regarding their reproductive health.